2018
DOI: 10.1016/j.jshs.2017.01.013
|View full text |Cite
|
Sign up to set email alerts
|

The association between Tai Chi exercise and safe driving performance among older adults: An observational study

Abstract: BackgroundAge-related cognitive and physical decline can impair safe driving performance. Tai Chi exercise benefits cognitive and physical function and may influence safe driving performance in older adults. The primary aim of this observational study was to compare cognitive processes and physical function related to safe driving performance among older adult Tai Chi practitioners to normative reference values. Secondary aims were to examine relationships between Tai Chi exercise habits, cognitive processes, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 43 publications
0
10
0
1
Order By: Relevance
“…The generalization of the present study’s results should, therefore, be interpreted with caution. Last, any moderators that may affect the effects of exercise on cognition should be considered (Kato et al, 2018; Miller and Taylor-Piliae, 2018). While acute exercise improves cognitive function, the improvement is larger for individuals with higher fitness compared to those with low fitness (Chu et al, 2015) or for those with low-income status than those with high-income status (Tine, 2014), suggesting that the relationship could be modulated by personal and environment characteristics.…”
Section: Discussionmentioning
confidence: 99%
“…The generalization of the present study’s results should, therefore, be interpreted with caution. Last, any moderators that may affect the effects of exercise on cognition should be considered (Kato et al, 2018; Miller and Taylor-Piliae, 2018). While acute exercise improves cognitive function, the improvement is larger for individuals with higher fitness compared to those with low fitness (Chu et al, 2015) or for those with low-income status than those with high-income status (Tine, 2014), suggesting that the relationship could be modulated by personal and environment characteristics.…”
Section: Discussionmentioning
confidence: 99%
“…However, there were no differences between judo and karate practitioners. A study with Tai-Chi practitioners aged 65 years and over revealed that they were more accurate and showed faster reaction times in a peripheral vision task than sedentary adults of the same age [73]. The results of that study also showed that Tai-Chi practitioners scored better on the rest of the subtests, which included visual search and cognitive tasks related to executive control.…”
Section: Visuospatial Attentionmentioning
confidence: 92%
“…Coordination training also improves cognitive functioning in older adults [28,51,60]. This type of exercise seems to be also involved in perceptual speed and in the visual-spatial network [28,60,72,73]. This is not surprising given that coordination activity is based on: balance, eye-hand and/or leg-arm coordination and spatial orientation skills, and it also may require interacting with persons and other objects in the environment.…”
Section: The Role Of Physical Exercise In Successful Agingmentioning
confidence: 98%
“…Exercise has been linked to enhanced cognitive functioning and reduced risk of cognitive impairment in animals (García-Mesa et al, 2011) and older humans (Netz et al, 2011; Behrman and Ebmeier, 2014; Frederiksen et al, 2015; Miller and Taylor-Piliae, 2018). The effects of exercise on cognitive function appear to be particularly beneficial to executive control.…”
Section: Introductionmentioning
confidence: 99%